2019
DOI: 10.1002/adma.201906508
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Hydrogel Based on PEO–PPO–PEO Poloxamers for a Controlled In Situ Release of Recombinant Adeno‐Associated Viral Vectors for Effective Gene Therapy of Cartilage Defects

Abstract: Advanced biomaterial‐guided delivery of gene vectors is an emerging and highly attractive therapeutic solution for targeted articular cartilage repair, allowing for a controlled and minimally invasive delivery of gene vectors in a spatiotemporally precise manner, reducing intra‐articular vector spread and possible loss of the therapeutic gene product. As far as it is known, the very first successful in vivo application of such a biomaterial‐guided delivery of a potent gene vector in an orthotopic large animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 29 publications
0
104
1
Order By: Relevance
“…Controlled release of the therapeutic SOX9 from the poloxamer gel improved repair of full-thickness chondral defects. 238 To further enhance adhesiveness of poloxamer 407 for local viral delivery to organ surfaces, it was blended with >1% polycarbophil, a polyacrylic acid cross-linked with divinyl glycol. Addition of polycarbophil changed the sol-gel transition temperature and led to higher adhesiveness due to numerous carboxylic groups, which can easily form bonds with surrounding molecules.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…Controlled release of the therapeutic SOX9 from the poloxamer gel improved repair of full-thickness chondral defects. 238 To further enhance adhesiveness of poloxamer 407 for local viral delivery to organ surfaces, it was blended with >1% polycarbophil, a polyacrylic acid cross-linked with divinyl glycol. Addition of polycarbophil changed the sol-gel transition temperature and led to higher adhesiveness due to numerous carboxylic groups, which can easily form bonds with surrounding molecules.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…Scaffold-assisted gene therapy is a powerful tool to durably and safely enhance the processes of cartilage repair [10][11][12] via single-step, controlled delivery of clinically adapted rAAV gene transfer vectors [25][26][27][28][29][30][31][32][33]. In the current work, we tested the ability of mechanically stable, biocompatible PCL scaffolds functionalized with a bioactive pNaSS molecule to transfer rAAV vectors coding for the cartilage-specific SOX9 transcription factor to human bone marrow aspirates as a means to generate more efficient, non-invasive systems to treat focal cartilage lesions compared with a less stable scaffold-free vector application lacking scaffolding benefits for the cell targets [42] or with complex, indirect transplantation of rAAV-modified aspirates via such materials [43].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, a number of studies reported the potential of applying rAAV for experimental cartilage research via hydrogel systems (alginate, fibrin, poloxamers/poloxamines, self-assembling peptides, polypseudorotaxanes) [25][26][27][28][29][30][31][32][33] while there is still little information on the potential benefits of solid, mechanically more stable biomaterials that may provide scaffolding and stability to the target cells [34] for rAAV-mediated gene transfer. In this regard, we recently provided evidence that biocompatible solid polyester poly(ε-caprolactone) (PCL) [35], an aliphatic polyester approved by the FDA [36,37], further grafted with poly(sodium styrene sulfonate) (pNaSS) to activate reparative cellular responses [38] is capable of supporting the delivery of reporter rAAV gene vectors to effectively modify human bone marrow aspirates [39].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the apparent absence of an immune response in all defects (lack of expression of CD3 for T-lymphocytes, of CD11b for activated macrophages, and of human leukocyte antigen isotype DR alpha—HLA-DRα—for class II major histocompatibility complex—MHC—antigens) supported the use of such PEO-PPO-PEO poloxamers to protect rAAV-mediated gene transfer from neutralization by antibodies directed against the AAV capsid. Although not directly applied to an osteochondral defect model, this study showed by a comprehensive analyses of the entire osteochondral unit that rAAV-FLAG-h sox9 /PEO-PPO-PEO hydrogel-augmented microfracture significantly improves osteochondral repair [ 151 ].…”
Section: Scaffold-mediated Viral In Vivo Gene Delivery For Osteochmentioning
confidence: 99%